Imaging of Ventriculoperitoneal Shunt Complications: Comparison of Whole Body Low-Dose Computed Tomography and Radiographic Shunt Series. Issue 6 (November 2016) - Afat, Saif; Pjontek, Rastislav; Hamou, Hussam A.; Herz, Klaus; Nikoubashman, Omid; Bamberg, Fabian; Brockmann, Marc A.; Nikolaou, Konstantin; Clusmann, Hans; Wiesmann, Martin; Othman, Ahmed E.
Abstract : Objective: To determine diagnostic value and radiation exposure of low-dose computed tomography (LD-CT) compared to radiographic shunt series (SS) for the detection of ventriculoperitoneal (VP) shunt complications. Methods: Fourteen VP shunts were implanted in 7 swine cadavers. Mechanical complications were induced in 50% of VP shunts. Low-dose CT (80 kVp, 10 mAs, Pitch = 1.5) and SS were acquired. Dose area product (DAP) and effective doses for SS and LD-CT were collected. Scoring of diagnostic confidence and blinded readings of SS and CT data were performed. Results: The sensitivity of LD-CT was high (0.97; 95% confidence interval, 0.91–1.00) with excellent interobserver agreement (κ = 0.88). Similarly, the sensitivity of SS was high (0.82; 95% confidence interval, 0.68–0.95) with good interobserver agreement (κ = 0.68). In contrast, LD-CT was associated with significantly higher diagnostic confidence (4.64 ± 0.41 vs 2.71 ± 0.73; P < 0.01) and significantly lower radiation exposure (effective dose: 0.26 mSv vs 1.06 mSv; DAP: 265.4 μGym 2 vs 724.8 μGym 2 ; P < 0.001). Conclusions: For the assessment of suspected VP shunt complications, LD-CT provides excellent sensitivity and higher diagnostic confidence with lower radiation exposure compared with SS.